Reducing Eating Disorder Onset in a Very High Risk Sample with Significant Comorbid Depression: A Randomized Controlled Trial - Taylor, C. Barr (J Consult Clin Psychol, 2016)
OBJECTIVE: Eating disorders (EDs) are serious problems among college-age women and may be preventable. An indicated on-line eating disorder (ED) intervention, designed to reduce ED and comorbid pathology, was evaluated. METHOD: 206 women (M age = 20 ± 1.8 years; 51% White/Caucasian, 11% African American, 10% Hispanic, 21% Asian/Asian American, 7% other) at very high risk for ED onset (i.e., with high weight/shape concerns plus a history of being teased, current or lifetime depression, and/or non-clinical levels of compensatory behaviors) were randomized to a 10-week, Internet-based, cognitive-behavioral intervention or wait-list control. Assessments included the Eating Disorder Examination (EDE to assess ED onset), EDE-Questionnaire, Structured Clinical Interview for DSM Disorders, and Beck Depression Inventory-II. RESULTS: ED attitudes and behaviors improved more in the intervention than control group (p = 0.02, d = 0.31); although ED onset rate was 27% lower, this difference was not significant (p = 0.28, NNT = 15). In the subgroup with highest shape concerns, ED onset rate was significantly lower in the intervention than control group (20% versus 42%, p = 0.025, NNT = 5). For the 27 individuals with depression at baseline, depressive symptomatology improved more in the intervention than control group (p = 0.016, d = 0.96); although ED onset rate was lower in the intervention than control group, this difference was not significant (25% versus 57%, NNT = 4). CONCLUSIONS: An inexpensive, easily disseminated intervention might reduce ED onset among those at highest risk. Low adoption rates need to be addressed in future research.